Women’s Education as a Divine Imperative: Comparative Reflections from Pakistan and Malaysia (Al-Aasar, 2025)
Education is a fundamental human right and a divine obligation in Islam. Rooted in the Quranic command to seek knowledge and the Prophetic emphasis on education for all, irrespective of gender, women’s education is a cornerstone for individual empowerment, family cohesion, and societal progress. This study delves into the theological underpinnings of women’s education in Islam and examines its contemporary relevance. Using Pakistan and Malaysia as comparative case studies, this research explores how cultural, political, and economic contexts influence educational opportunities for women in these Islamic societies. The study employs a mixed-methods approach, utilizing qualitative and quantitative data from policy documents, official statistics, and field research. Findings reveal that while both countries recognize the importance of women’s education, their progress diverges due to socio-economic challenges, cultural norms, and governance structures. Malaysia has successfully integrated Islamic principles with modern educational frameworks, achieving higher literacy and gender parity. Meanwhile, Pakistan struggles with systemic barriers such as rural-urban disparities and socio-cultural constraints. The paper concludes by recommending strategies to enhance educational policies and align them with Islamic teachings, ensuring women’s empowerment as envisioned by divine principles.